A Simplified Analog Implementation of Cyclic Shift Chirp Encoding and Decoding for LoRa Communications - Saelim, Nopparut; Tuwanut, Panwit; Pornavalai, Chotipat (My University, 2026)
Currently, LoRa wireless communication technology has become widely adopted in IoT systems due to its long-range capability and low power consumption. However, LoRa is a technology developed by Semtech, which does not disclose the details of the Cyclic Shift Chirp encoding process, a core component of LoRa signals. This lack of transparency prevents users from accessing the physical-layer structure of the signal or freely customizing key parameters such as bandwidth and spreading factor. Although such customization can enhance system flexibility, there is currently no officially disclosed method to achieve it. This research proposes a Cyclic Shift Chirp encoder/decoder circuit built from basic analog components, including adders, subtractors, comparators, and ramp generators, based on a Pulse Width Modulation (PWM) principle. This approach enables researchers and developers to generate LoRa-like signals independently and customize various parameters without introducing limitations. Moreover, the proposed circuit is simple, low-cost, and easy to understand, making it suitable for advanced research, educational experiments, and the design of communication systems that require high flexibility at the LoRa PHY layer.
Keywords: analog circuit; Cyclic Shift Chirp; decoding; encoding; IoT communications; LoRa; PWM